2018
DOI: 10.1073/pnas.1722086115
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the membrane domain of ATP synthase in human mitochondria

Abstract: The ATP synthase in human mitochondria is a membrane-bound assembly of 29 proteins of 18 kinds. All but two membrane components are encoded in nuclear genes, synthesized on cytoplasmic ribosomes, and imported into the matrix of the organelle, where they are assembled into the complex with ATP6 and ATP8, the products of overlapping genes in mitochondrial DNA. Disruption of individual human genes for the nuclear-encoded subunits in the membrane portion of the enzyme leads to the formation of intermediate vestigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
187
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(204 citation statements)
references
References 36 publications
15
187
0
2
Order By: Relevance
“…The graphs were generated as in Fig 3, but in this case, the peptide intensity values for the individual subunits belonging to each module (He et al, 2018) were averaged to simplify the analysis. The graphs were generated as in Fig 3, but in this case, the peptide intensity values for the individual subunits belonging to each module (He et al, 2018) were averaged to simplify the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The graphs were generated as in Fig 3, but in this case, the peptide intensity values for the individual subunits belonging to each module (He et al, 2018) were averaged to simplify the analysis. The graphs were generated as in Fig 3, but in this case, the peptide intensity values for the individual subunits belonging to each module (He et al, 2018) were averaged to simplify the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A Complexome profiles of the two cV structural and assembly modules. The graphs were generated as in Fig 3, but in this case, the peptide intensity values for the individual subunits belonging to each module (He et al, 2018) were averaged to simplify the analysis. The represented values are the mean AE SEM of the two reciprocal labeling experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this model still stands true in principle, recent studies on the mammalian enzyme challenged some of the assumptions. By systematically knocking out subunits e, f, g, DAPIT, MLQ (He, Ford et al 2018) and c (He, Ford et al 2017) Walker and coworkers demonstrated some level of variability regarding incorporation of individual modules. Thus, vestigial (and catalytically non-functional) complex can assemble without the c-ring, although the formation of F1-c module probably represents standard assembly intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Pulse labeling with stable isotopes of essential amino acids can distinguish newlysynthesized proteins from pre-existing copies. We grew HeLa cells in "light" medium containing 12 C-lysine and arginine and switched to medium with lysine and arginine containing six 13 C residues in each to initiate pulse labeling, continued growth for defined time periods and isolated mitochondria and/or respiratory chain complexes. Labeling with stable isotopes enables mass spectrometric detection of the heavy:light or H:L ratio of a large fraction of the mitochondrial proteome as an index of the synthesis rate for a far greater number of proteins than in a radioactive labeling experiment.…”
mentioning
confidence: 99%